2011
DOI: 10.1063/1.3616142
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent photoluminescence from chemically and thermally reduced graphene oxide

Abstract: Temperature-dependent photoluminescence (PL) of graphene oxide (GO) reduced with hydrazine and heat has been measured to investigate the effect of reduction type on the bandgap of the reduced GO. Nitrogen functionalities formed in the hydrazine-treated GO were responsible for a strong localization of carriers that caused in a fluctuation in PL peak position with temperature. The intensity of C-OH peak was relatively low in the heat-treated GO, indicating that raising temperature facilitated the removal of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…X-ray photoelectron spectroscopy (XPS) can provide information about the surface functional groups and hence can distinguish the surface composition of CNDs, quasi CNDs and aggregated molecular fluorophores 18 . Finally, quantitative information about the contribution of the fluorophore in the optical properties in quasi CNDs can be obtained by in situ temperature dependent (following the same thermal stability of the fluorophore) photoluminescence measurements using confocal Raman spectroscopy 19 . The destruction of the fluorophore of the quasi CNDs will decrease the photoluminescence substantially.…”
Section: Guidelines To Characterizing Carbogenic Nanodotsmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) can provide information about the surface functional groups and hence can distinguish the surface composition of CNDs, quasi CNDs and aggregated molecular fluorophores 18 . Finally, quantitative information about the contribution of the fluorophore in the optical properties in quasi CNDs can be obtained by in situ temperature dependent (following the same thermal stability of the fluorophore) photoluminescence measurements using confocal Raman spectroscopy 19 . The destruction of the fluorophore of the quasi CNDs will decrease the photoluminescence substantially.…”
Section: Guidelines To Characterizing Carbogenic Nanodotsmentioning
confidence: 99%
“…The chemical structure of GO is a matter of ongoing discussion with a number of models proposed -for a summary see Dreyer et al (2010); Zhao et al (2015). In experiments by Cuong et al (2011) thermal reduction at 700 • C resulted in removal of many oxygen-containing groups illustrated in figure 3, but with carbonyl groups being persistent. Li et al (2012) have found that GO samples with high levels of carbonyl groups produce PL with the best spectral match to ERE.…”
Section: Go Nanoparticles and Erementioning
confidence: 99%
“…Schematic illustration of GO showing sites of oxygencontaining groups in as-produced (modified Hummers method) GO(Cuong et al 2011). Hydrogen atoms (C-H) are omitted for clarity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene has attracted tremendous interest in recent years because of its extraordinary properties including optical 1 and electrical conductivity, 2 mechanical strength, 3 thermal conductivity, 4-7 electron emisibility, 8 the unexpected edge states, and its potential device applications at the nanoscale. 4,[9][10][11] Overwhelming contributions have been made to explore the lattice dynamics using Raman spectroscopy under various conditions such as temperature (T), [12][13][14][15][16][17][18][19][20] pressure (P), 21 and substrate conditions. 22 Generally, the Raman shifts of graphene are softened by heating and stiffened by high-pressure compression.…”
mentioning
confidence: 99%